1998
DOI: 10.5694/j.1326-5377.1998.tb123367.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with waiting time for surgery

Abstract: Objective To explore the factors associated with waiting times for surgery in public hospitals. Setting Three major acute care public hospitals in one Area Health Service. Participants 691 adult patients entered onto the computerised booking list between 16 and 22 November 1994, and then between 16 January and 12 February 1995, were interviewed prospectively and followed up over a minimum of 18 months. Data were obtained from the Area Health Service's computerised booking system and patient self‐report. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The relationship between severity of illness and waiting time for elective surgery has previously been shown to be tenuous 6−8 . A study conducted in an area health service in New South Wales has shown that although waiting time was strongly associated with the urgency rating given by the surgeon 7 a number of other factors − surgical specialty, health insurance status and employment status − appeared to exert an additional and independent influence on waiting time. Informal guidelines for prioritizing urgency of surgery have existed for some years but none has gained national acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between severity of illness and waiting time for elective surgery has previously been shown to be tenuous 6−8 . A study conducted in an area health service in New South Wales has shown that although waiting time was strongly associated with the urgency rating given by the surgeon 7 a number of other factors − surgical specialty, health insurance status and employment status − appeared to exert an additional and independent influence on waiting time. Informal guidelines for prioritizing urgency of surgery have existed for some years but none has gained national acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Clover et al . used a similar approach to look at urgency rating's effect on waiting in Australia 11 . There is a need for research that is outcome related 12 − research that not only looks at how people get on the ‘list’ but also the impact of waiting and how they get off the ‘list’.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, lengthening of waiting lists for elective surgery and medical procedures has become a common feature in most publicly funded health‐care systems worldwide 1−5 . The major contributing factors to the existence of waiting lists include the discrepancy between demand and supply of medical services in which access to health care is free, ageing of the population, and the availability of new technology and treatments 4,6 .…”
Section: Introductionmentioning
confidence: 99%